The influence of eye model parameter variations on simulated eye-tracking outcomes - Joshua Fischer; David van den Heever; Johan van der Merwe (Bern Open Publishing, 2023)
The simulated data used in eye-tracking-related research has been largely generated using normative eye models with little consideration of how the variations in eye biometry found in the population may influence eye-tracking outcomes. This study investigated the influence that variations in eye model parameters have on the ability of simulated data to predict real-world eye-tracking outcomes. The real-world experiments performed by two pertinent comparative studies were replicated in a simulated environment using a high-complexity stochastic eye model that includes anatomically accurate distributions of eye biometry parameters. The outcomes showed that variations in anterior corneal asphericity significantly influence simulated eye-tracking outcomes of both interpolation and model-based gaze estimation algorithms. Other, more commonly varied parameters such as the corneal radius of curvature and foveal offset angle had little influence on simulated outcomes.